2022
DOI: 10.1155/2022/3970884
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a History of Different Other Cancers on the Long-Term Outcomes of Patients with Intrahepatic Cholangiocarcinoma: A Population-Based Analysis

Abstract: Background. The characteristics and outcomes of patients with intrahepatic cholangiocarcinoma (ICC) with prior malignancy are poorly clarified. This study is aimed at exploring the impact of prior malignancy on the long-term outcomes of ICC patients. Methods. Using the Surveillance, Epidemiology, and End Results (SEER) program, ICC patients diagnosed between 2004 and 2018 were identified. Kaplan-Meier curves and Cox analysis were used to evaluate the impact of prior malignancy on the prognosis of ICC patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…27,28 The Kaplan-Meier, Multivariable Cox regression analysis and Subgroup analysis showed a decrease in the specific mortality of gallbladder cancer in patients with a history of previous cancer, aligning with the previous findings in other cancer types. 18,29 These studies showed an increased risk of death from previous cancer or non-cancer causes when compared to patients without a previous cancer history. Subgroup stratified analysis further showed that the previous cancer history may act as a protective factor against specific mortality of gallbladder cancer, except in cases where the tumor size > 6, stage II and stage III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The Kaplan-Meier, Multivariable Cox regression analysis and Subgroup analysis showed a decrease in the specific mortality of gallbladder cancer in patients with a history of previous cancer, aligning with the previous findings in other cancer types. 18,29 These studies showed an increased risk of death from previous cancer or non-cancer causes when compared to patients without a previous cancer history. Subgroup stratified analysis further showed that the previous cancer history may act as a protective factor against specific mortality of gallbladder cancer, except in cases where the tumor size > 6, stage II and stage III.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Another study also showed that a history of cancer has no significant impact on the prognosis of patients with intrahepatic cholangiocarcinoma. 18 However, in the case of laryngeal and gastric cancers, previous cancer history has been found to adversely affect prognosis. 19,20 Despite these findings, the influence of a prior cancer diagnosis on the prognosis of patients with gallbladder cancer remains understudied and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%